How feasible and practical is it to introduce the Endometriosis Phenome and Biobanking Harmonisation Project (EPHect) standard surgical form into clinical practice?. Issue 4 (December 2018) - To, Valerie; Lam, Alan; Shyamsunder, Akshara; Johnson, Neil
Background: The Endometriosis Phenome and Biobanking Harmonisation Project has been set up to facilitate and advance global endometriosis research. Aim: To test the feasibility and practicality of using the Endometriosis Phenome and Biobanking Harmonisation Project standard surgical form in routine clinical practice. Materials and methods: Standard surgical form was filled out using a web-based application for 225 consecutive women who underwent surgery for suspected or known endometriosis. Results: Median age was 37 years. Half (49.8%) of the women had a previous surgical diagnosis of endometriosis. Endometriosis was found in 91.5% of patients in this cohort. Median operative time was 101 min. Operative photographs substantially assisted completion of the standard surgical form post-operatively. The median time required to fill out the questionnaire was 8 min (range, 2–17 min). This was mostly dependent on the severity and distribution of endometriosis lesions. The standard surgical form is very comprehensive and has the advantage of including both the American Society of Reproductive Medicine classification and the Endometriosis Fertility Index; however, characterisation of deep endometriosis is insufficient for some women. In addition, some sections such as the descriptive endometriosis table (section IX) remain subjective. Conclusion: Using the Endometriosis Phenome and Biobanking Harmonisation Project standard surgical form to collect research data is feasible, especially when using an electronic database entry tool. It is also practically manageable, although the time taken is more than originally estimated by the Endometriosis Phenome and Biobanking Harmonisation Project standard surgical form authors. Even though some sections of the standard surgical form may be subjective, it is comprehensive and we would recommend its adoption into routine clinical practice for endometriosis research.